The disciplinary proceeding – reflections on the Resolutions of the Supreme Court I KZP18/12 of 24 January 2013 - Kusowska, Ewelina (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2014)
The aim of the study it to discuss the issue of disciplinary proceeding in the context of entity subject to disciplinary liability, the subject matter, the autonomy and the purpose. The author focuses on the ruling of the Supreme Court passed on January 24th 2013, which suggests the application of the rules of criminal proceedings as more appropriate for the subsidiary application of the disciplinary proceedings. Nevertheless the Supreme Court draws attention to another, equally important issue which became apparent in connection with the above – the diversity and lack of consistency of solutions used by the legislature pursuant to a disciplinary proceedings.